Performance of Municipal Cycling Policies in Medium-Sized Cities in the Netherlands since 2000. Issue 1 (2nd January 2016) - Harms, Lucas; Bertolini, Luca; Brömmelstroet, Marco Te
Abstract: With its high cycling mode share, the Netherlands is often seen as a best practice for cycling policies. However, there is little insight into the drivers behind this phenomenon, specifically which policy interventions increased cycling rates and which did not. The knowledge gap on the effectiveness of cycling policies seriously limits the potential for learning from the Dutch experience. This paper will address this gap, by exploring the performance of Dutch cycling policies in 22 medium-sized cities since 2000. First, the existing ideas regarding the effectiveness of cycling policy are reviewed. These insights structure the exploration of data from Statistics Netherlands and the Dutch Cyclists' Union, complemented with a survey of local policy-makers by means of an explorative data-mining methodology called rough set analysis. Our findings support the following hypotheses regarding the performance of cycling policy in Dutch cities: first of all, the way cycling policy is implemented seems important: setting measurable and verifiable goals, following through with most of the proposed policy interventions, allowing for experimental measures to be explored and showing strong leadership. Second, providing adequate cycling infrastructure and decreasing the attractiveness of car use (e.g. by increasing parking tariffs and increasing the area of paid on-street car parking) seem to be key drivers. Finally, we found that external circumstances, such as demographic trends, seem to influence cycling policy outcomes. Future research is needed to test these hypotheses.